One LIVING IN THE COUNTRYSIDE OR IN THE CITY: WHAT CHANGES IN BODY COMPOSITION AND STRENGTH? (Fiep Bulletin - online, 2024)
Introduction: This document explores the differences between residents of urban and rural areas regarding health and functional capacity. Urban areas offer greater access to healthy food and sports activities, while rural areas have food autonomy but may face limitations in improving strength and functional capacity. This specific study compares muscle strength and Body Mass Index (BMI) among urban and rural residents over the age of 45. Objective: To compare strength and Body Mass Index (BMI) among urban and rural residents over the age of 45. Methods: The study adopted a cross-sectional and analytical approach, with convenience sampling. Participants underwent hand grip strength tests and sit-to-stand tests. Additionally, anthropometric data were collected, and semi-structured interviews were conducted to gather relevant information. Results: The sample consisted of 68 participants, with 49 urban residents and 19 rural residents. Both groups exhibited average BMIs indicative of overweight. However, no significant differences in isometric strength were found between the groups. Urban residents showed slightly better performance in the lower limb endurance test. Conclusion: It can be concluded that individuals in both regions are susceptible to the risks associated with overweight and physical inactivity.
Keywords: Urban and rural health; Muscle strength; Body Mass Index; physical inactivity